Implementasi Kebijakan Pembuatan Surat Tanda Registrasi (STR) Bagi Tenaga Kesehatan Provinsi Kalimantan Tengah - Bulkani Bulkani; Agus Harianto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
A person who has graduated and holds a degree in healthcare personnel, before contact directly with the community or provides public services and according to the health LAW mandate must have a registration letter/STR. Based on the initial survey in STR making still, have complaints or difficulties from the applicant medical personnel registration and considering the area and payment through the Bank becomes a separate obstacle for health workers in obtaining the registration letter. This research is to find out how the registration policy is implemented in the provincial health office of Central Kalimantan and the factors affecting the policy. Four factors influencing the implementation of the policy according to the theory of George C. Edward III, namely: communication, resources, disposition, and bureaucratic structure. The method used is a qualitative determination of the descriptive snowball informant while the key informant is a section of the head of the HUMAN Data collection techniques with observation, interviews, and documentation. The results of this study concluded that the implementation of the Register of registration letter policy has been executed in accordance with the mandate of law and regulation of the Minister of Health, but not in accordance with what is expected by the public, because there are Factor IE resources, especially the source of funds and facilities are still limited, servers are often disruptions. So even though the human resources are adequate, communication factors are good, the disposing factor and bureaucratic structure are also good, but if not supported by resources and facilities are adequate especially the source of funds then the policy Can not be implemented properly.